Twinkle artefact in the ultrasound diagnosis of superficial epidermoid cysts - Clarke, Richard (Ultrasound, 2016)
AIM: The aim of the study was to evaluate whether the twinkle artefact is a valuable feature in the sonographic diagnosis of superficial epidermoid cysts. MATERIALS AND METHODS: A retrospective search was undertaken of our institution’s Radiology Information System and pathology database to identify cases of superficial masses showing the twinkle artefact that proceeded to surgical excision. RESULTS: Eighteen superficial masses demonstrating the twinkle artefact were identified that were submitted for pathological analysis. Of these, 17 were confirmed to represent epidermoid cysts and only 1 case had an alternative diagnosis (proliferating trichilemmal cyst). CONCLUSION: The presence of the twinkle artefact appears to be a specific and valuable ancillary sonographic feature for the diagnosis of superficial epidermoid cysts.